AN ANAYLYSIS OF DIRECTIVE SPEECH ACTS IN BEAUTY AND THE BEAST MOVIE SCRIPT - Cornela, Angelisha; Sari, Dian Purnama (STBA Prayoga Padang, 2024)
This article aimed to analyze types of directive speech act found in movie script Beauty andthe Beast. Directive speech act itself is a speech act in which speaker attempts to persuade thehearer or partner to perform an act or do something (or not do something). The researchersfocused on type of directive speech act found in the movie script.The researchers used theoryof Searle to classify the types of directive speech act which are commanding, requesting,inviting, forbidding, and suggesting. The researcher then marked and took a note theutterances data found in the script. After doing this inquires about, the researchers found allthe types of directive speech act that mentioned by Searle with 59 data. The types of directivespeech act dominated in the movie script is commanding with 30 data and followed byrequesting and forbidding with 11 data each. The next is suggesting with 6 data and the leastis inviting with 1 data. The researcher hopes can add insight in the field of linguistics.